The Impact of an Accelerator Program for Startup to Develop the Business in Circular Economy - Andreas Pandu Wirawan; Susy Muchtar; Febria Nalurita (Journal of Social Research, 2023)
The economic transition from a linear to a circular economy is considered very important, especially to reduce the environmental impact that has been generated due to waste. One way to accelerate the transition is through the opening of new jobs through startups. Startups that are starting to grow their business need to get a variety of support. Therefore, the acceleration program is here to help business development while fostering innovation in the circular economy sector. The purpose of this study is to analyze the influence of modules and learning, mentorship and mentoring, access to funding, and the network of cooperation provided by the Circular Jumpstart acceleration program to startups in the circular economy. This research uses a qualitative method by analyzing data obtained from questionnaires and the process of in-depth interviews. The results obtained in the research of the Circular Jumpstart acceleration program have a positive and significant effect on the business development of startups in the circular economy. Developments resulting from the provision of modules and learning, mentors and mentoring, access to capitalization, and cooperation networks to Circular Jumpstart participants. From the results obtained, it is known that modules and learning, mentors and mentoring, access to capital, and cooperation networks provided in the Circular Jumpstart program have a positive effect on the development of start-up businesses in the circular economy sector. As for being able to have a positive impact, the Circular Jumpstart acceleration program needs to develop access to government agencies, as well as provide a one-on-one mentoring method to better adapt to the needs of startups.